Investigation of the frequency of COVID-19 in patients treated with intravesical BCG - Karabay,Oğuz (2020)
SUMMARY INTRODUCTION In this retrospective study, we aimed to investigate the frequency of COVID-19 in patients with and without BCG application due to bladder tumors. METHODS The presence of COVID-19 was investigated in 167 patients with BCG and 167 without bladder cancer. All patients were compatible with COVID-19 infection. Patients with RT-PCR positive for SARS-CoV-2 and/or Chest CT positive for viral pneumonia between March and May 2020 were included in the study. RESULTS A total of 334 patients were included in the study. The mean age of the 167 patients in the study group was 71.1±14.2 1 (min. 38.0– max. 98.0 years), 141 (84.4%) were male. The mean age of the 167 patients in the control group was 70.5±13.8 years (min. 41.0– max. 96.0 years), and 149 were male (p> 0.05). COVID-19 was detected in 5 patients in the BCG group and in 4 patients in the control group (P> 0.05). CONCLUSION Intravesical BCG administration does not decrease the frequency of COVID-19 infection.